2016
DOI: 10.4103/0975-7406.199342
|View full text |Cite
|
Sign up to set email alerts
|

Averrhoa bilimbi Linn.: A review of its ethnomedicinal uses, phytochemistry, and pharmacology

Abstract: Averrhoa bilimbi Linn. is principally cultivated for medicinal purposes in many tropical and subtropical countries of the world. Literature survey about this plant shows that A. bilimbi is mainly used as a folk medicine in the treatment of diabetes mellitus, hypertension, and as an antimicrobial agent. The prime objective of this review is to accumulate and organize literature based on traditional claims and correlate those with current findings on the use of A. bilimbi in the management of different ailments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 29 publications
1
25
0
1
Order By: Relevance
“…XRD studies The synthesized TiO 2 nanoparticles using Averrhoa bilimbi fruits extract were analyzed by x-ray diffraction spectroscopy. In this figure 1, showed the XRD analysis of synthesized TiO 2 diffraction peaks at 25 [31]. The average crystalline size of green synthesized TiO 2 nanoparticles was found to be 23.8 nm.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…XRD studies The synthesized TiO 2 nanoparticles using Averrhoa bilimbi fruits extract were analyzed by x-ray diffraction spectroscopy. In this figure 1, showed the XRD analysis of synthesized TiO 2 diffraction peaks at 25 [31]. The average crystalline size of green synthesized TiO 2 nanoparticles was found to be 23.8 nm.…”
Section: Resultsmentioning
confidence: 87%
“…TiO 2 is an n-type semiconductor with an energy band gap of 3.2 eV. Averrhoa bilimbi is one of the medicinal plants which are used for the treatment of diabetes, hypertension and act as an anticancer and antimicrobial agent [25]. From phytochemical studies, it is found to contain phenol, flavonoids and tannins.…”
Section: Introductionmentioning
confidence: 99%
“…The leaves and fruits of Averrhoa bilimbi were found to be cytotoxic against MCF-7 breast cancer cell lines (IC 50 was 154.9 and 668 µg/mL for fruits and leaves, respectively) [98]. The major bioactive phytoconstituents included nonanal, tricosane, squalene, and malonic acid [99].…”
Section: Oxalidaceaementioning
confidence: 99%
“…Decoctions, infusions, powders, and pastes have been used in several traditional medicinal systems including those in Suriname for preventing and treating many diseases such as skin eruptions, cough, cold, syphilis, diarrhea, obesity, diabetes mellitus, microbial infections, and hypertension [46,178]. Physicochemical and pharmacological studies supported some of these uses [179].…”
Section: Oxalidaceae -Averrhoa Bilimbi Lmentioning
confidence: 99%